Food Preferences in Two Detritivore Species: Laboratory Choice Tests Using Leaf Litters of Different Tree Species - Gabriela Makulec; Krassimira Ilieva-Makulec (Studia Ecologiae et Bioethicae)
Soil fauna, including terrestrial isopods, millipedes and earthworms, play an important role in the decomposition of litter through the process of shredding it during consumption. In the present study, the food preferences in two detritivores, the common woodlouse (Oniscus asellus) and the earthworm (Lumbricus rubellus) over the leaf litter of four common tree species: common black alder (Alnus glutinosa), silver birch (Betula pendula), small-leaved linden (Tilia cordata) and pedunculate oak (Quercus robur) were quantified in the laboratory. For each animal species, two sets of feeding mesocosms were prepared: one set with single litter species and another with mixed litter material (cafeteria-type test), where the animals were allowed to choose among the four litter species at once. The food preferences of the studied animals were determined on the basis of the consumption (mass loss) of litter for each litter species at the end of two-weeks lasting experiments. The results showed that the litter mass losses in both detritivores were significantly influenced by the tree species. The litter mass losses can be ranked in descending order as follows: alder, birch, linden, oak. In the case of O. asellus, litter mixing had no effect on litter mass loss when compared to single alder and birch litter, however mixing clearly accelerated litter mass loss compared to single lime or oak litter. For L. rubellus, litter mixing was found to slow litter mass loss compared to each single alder, birch and lime litter, while accelerating litter mass loss compared to single oak litter. For the interpretation of the results, the literature data on carbon to nitrogen ratio, as well as the proportion of difficult-to-degrade polyphenols and lignins in leaves of the studied tree species were used.